(untitled) (Journal of the College of Basic Education, 2022)
With the revolution of information technology and Wide Area Networking, data has become less and less private where the accesses of media as well as the attempts to change and manipulate the contents of media data have become a common case. For that, we need to use a watermarking technique to protect the copyright of the media as well as for digital right management but without leaving a visual effect. [1